2022
DOI: 10.3389/fnut.2022.853118
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Na, K, and Lipid Intake in Each Meal and Blood Pressure

Abstract: Cardiovascular diseases (CVDs) are one of the leading causes of death worldwide, and one of the most significant risk factors for CVDs is high blood pressure. Blood pressure is associated with various nutrients, such as sodium, potassium, and cholesterol. However, research focusing on the timing of intake of these nutrients and blood pressure has not been conducted. In this study, we used dietary data and a questionnaire asking about the sleep, physical activity, and blood pressure, collected from the food-log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…The intake timing of snacks might have been different among participants because the snack time was not checked in this study. In our previous study, the validity of the dietary record of this app was high [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intake timing of snacks might have been different among participants because the snack time was not checked in this study. In our previous study, the validity of the dietary record of this app was high [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested that habitual breakfast skipping is related to health problems such as the risk of obesity [ 4 ], cardiovascular diseases [ 5 ], and cognitive function [ 6 ]. A survey of feeding patterns in Japan reported that many people have a meal ratio (10 for whole day’s energy intake) of 2.5 for breakfast; 3, lunch; and, 4.5, dinner [ 7 ]. At dinner, obesity is positively related to not only the energy quantity of meals but also the eating time of meals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that habitual breakfast skipping is related to health problems such as the risk of obesity [4], cardiovascular diseases [5], and cognitive function [6]. A survey of feeding patterns in Japan reported that many people have a meal ratio (10 for whole day's energy intake) of 2.5 for breakfast; 3, lunch; and, 4.5, dinner [7]. At dinner, obesity is positively related to not only the volume of meals but also the eating time of meals.…”
Section: Introductionmentioning
confidence: 99%